Carotenoid and chlorophyll content of Vitis vinifera cv. Merlot grapes during ripening with reference to variability in grapevine water status and vigour - Kamffer, Zindi (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2010.